The Woodenest. Stadium by ZHA in the South-West of England - Frolova, Nina (project baikal, 2017)
The Forest Green Rovers Stadium (Stroud, UK) designed by Zaha Hadid Architects will be built almost entirely of wood – the first time that will have been done anywhere in the world. The use of wood will ensure reduction of carbon dioxide emissions. Being a renewable resource, wood will also enhance the ecological characteristics of the building. The stadium’s roof is covered with a transparent membrane, which minimizes shadows and does not prevent the growth of grass on the stadium. The position of all the seats provides excellent views of the field. The first stage of building is planned for 5,000 spectators, increasing to 10,000 at the second stage. The stadium will be a part of the Eco Park development with the total area of 40 ha.